2-D and 3-D ultrasonographic characteristics of the ovary in women with PCOS and multifollicular ovaries. (18th August 2021) - Bozkurt, Murat; Kara Bozkurt, Duygu; Kurban, Didem; Takmaz, Taha; Sevket, Osman; Ozcan, Pinar
Abstract: In this prospective study, seventy-six patients (PCOS group; n = 36, multifollicular ovary group; n = 40) were evaluated by 2-D and 3-D ultrasonography. VOCAL programme, echogenicity, number of follicles and blood flow parameters were evaluated. The patients with PCOS had a higher total ovarian volume, mean stromal volume and stromal echogenicity (18.6 ± 4.75 to 10.2 ± 3.4 p  < .01; 12.23 ± 2.53 to 5.02 ± 2.44 p  = .02; score 1:28 to 10 p  < .01, respectively). There was no statistically significant difference in terms of mean RI and PI values between the groups ( p  > .05). 3 D power Doppler parameters included VI, FI, and VFI values of the patients with PCOS were higher when compared to those of the patients with multifollicular ovary (3.82 ± 2.65 to 1.78 ± 1.2, p  < .01; 50.76 ± 4.45 to 40.6 ± 3.64, p  = .03; and 2.34 ± 1.02 to 1.12 ± 0.65, p  = .02, respectively). Our results revealed that total ovarian volume, stromal volume and echogenicity; VFI, VI, and FI could be useful for differential diagnosis in women with PCOS and multifollicular ovaries. Impact statement: What is already known on this subject? Ultrasonography is considered the new diagnostic tool for PCOS. Enlarged ovaries with multiple small follicles peripherally located around increased ovarian stroma with increased stromal echogenicity are the sonographic features of polycystic ovaries. What do the results of this study add? 3-D Doppler ultrasonography may be more specific in the determination of multifollicular and polycystic ovaries when compared to RI and PI in 2-D Doppler ultrasonography. Moreover, 3-D power Doppler ultrasonography could be useful for differential diagnosis in women with PCOS and multifollicular ovaries. What are the implications of these findings for clinical practice and/or further research? In clinical practice, the differentiation of multifollicular ovaries and polycystic ovaries (PCO) is difficult with the use of 2-D sonography alone. Therefore, 3-D ultrasound and power Doppler may also be used in addition to 2-D ultrasound for the differentiation of multifollicular ovaries and PCO.